2010
DOI: 10.1007/s11064-010-0183-6
|View full text |Cite
|
Sign up to set email alerts
|

Intranasal Administration of Nerve Growth Factor Produces Antidepressant-Like Effects in Animals

Abstract: Many works showed that nerve growth factor (NGF) injected into the brain of animal model emerges potential antidepressant effects. However, this route of administration significantly restricts the application of NGF clinically. Here, we reported that intranasal NGF could provide an alternative to intraventricular injection. The behavioral analysis showed that intranasal administration of NGF reduced the immobility time in forced swimming test (FST) and tail suspension test (TST) in mice. Likewise, intranasal N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 31 publications
(33 reference statements)
0
26
0
Order By: Relevance
“…This different onset of action probably originates from dissimilar pharmacokinetics and targeting efficiencies of intranasally vs ICVadministered drugs (Thorne et al, 1995(Thorne et al, , 2008Shi et al, 2010). As at 30 min after intranasal application of Cy3-NPS, a much weaker signal was observed than after ICV injection, it is possible that, although NPS does reach the brain rapidly after transnasal delivery, it may require additional time to reach its brain target cells in the full concentration required to produce behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…This different onset of action probably originates from dissimilar pharmacokinetics and targeting efficiencies of intranasally vs ICVadministered drugs (Thorne et al, 1995(Thorne et al, , 2008Shi et al, 2010). As at 30 min after intranasal application of Cy3-NPS, a much weaker signal was observed than after ICV injection, it is possible that, although NPS does reach the brain rapidly after transnasal delivery, it may require additional time to reach its brain target cells in the full concentration required to produce behavioral effects.…”
Section: Discussionmentioning
confidence: 99%
“…Within the frontal cortical regions, several studies have revealed CMS-induced reductions in either 5-HT content itself (Vancassel et al, 2008; Sheikh et al, 2007; Li et al, 2003, 2009a; Yalcin et al, 2008; Yi et al, 2008; Xu et al, 2008; Rasheed et al, 2008; Vitale et al, 2009; Ahmad et al, 2010; Shi et al, 2010) or reductions in 5-HT turnover (Bekris et al, 2005). However, there have also been contradictory reports of CMS having no effect on 5-HT content or turnover in the frontal cortex (Dalla et al, 2005; Haidkind et al, 2003; Tannenbaum and Anisman, 2003; Johnson and Yamamoto, 2009, 2010; Dang et al, 2009b; Patterson et al, 2010; Laugeray et al, 2010).…”
Section: Neurochemical Systemsmentioning
confidence: 99%
“…Specifically, exposure to CMS reduces both 5-HT content (Vancassel et al, 2008; Sheikh et al, 2007; Li et al, 2003, 2009a; Yi et al, 2008; Xu et al, 2008; Rasheed et al, 2008; Ahmad et al, 2010; Shi et al, 2010; Kang et al, 2005; Chen et al, 2009; Zhang et al, 2004) and turnover [in females only; (Dalla et al, 2005)]. There is no effect of CMS on 5-HT transporter binding sites (Lopez et al, 1998) or protein levels (Cunningham et al, 2009), suggesting that these effects are likely due to changes in metabolism/catabolism rather than synaptic clearance.…”
Section: Neurochemical Systemsmentioning
confidence: 99%
“…Chronic administration of adrenocorticotropic hormone (ACTH) implemented by Kitamura et al (2002) is a method that provides some insight into the neurobiological mechanisms through which tricyclic antidepressant efficacy can be disrupted. In addition to the high levels of CRH and ACTH, serotonin (5-HT), toxic metabolites of kynurenine (KYN), their enzyme of activation (indoleamine 2,3-dioxygenase (IDO)) and proteins related to neurogenesis (brain-derived neurotrophic factor (BDNF) and nerve growth factor (NGF)) have been postulated to play an important role in the pathogenesis of depression (Laske et al, 2010;Pandey et al, 2002;Shi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%